Problems in foreign language teaching at non-linguistic school of higher learning and ways of their solution - Sazanova, L. S.; Rusanova, L. I.; Сазанова, Л. С.; Русанова, Л. І.; ORCID: http://orcid.org/0000-0002-3722-2593; ORCID: http://orcid.org/0000-0001-6239-2028 (Актуальные научные исследования в современном мире. – 2018. – Вып. 10 (42), ч. 5. – С. 17-19, 2018)
У статті визначено декілька проблем навчання іноземної мови у немовних вищих навчальних закладах, виявлені фактори, що впливають на процес навчання, і пропонуються шляхи їх вирішення.

The paper identifies several problems of foreign language teaching at non-linguistic higher education universities, identifies the factors that influence the process of learning and suggests the ways of their solution.

В статье определены несколько проблем обучения иностранному языку в неязыковых вузах, выявлены факторы, влияющие на процесс обучения, и предлагаются пути их решения.
Проблеми навчання іноземної мови у немовному ВНЗ та шляхи їх вирішення
Проблемы обучения иностранному языку в неязыковом вузе и пути их решения
Sazanova, L. S. Problems in foreign language teaching at non-linguistic school of higher learning and ways of their solution / Sazanova Larysa Serhiivna, Rusanova Liubov Ivanivna // Актуальные научные исследования в современном мире. – 2018. – Вып. 10 (42), ч. 5. – С. 17-19.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; вивчення іноземних мов; изучение иностранных языков; teaching foreign languages; higher education; foreign language; foreign language teaching; profession-oriented teaching; proficiency; вища освіта; іноземна мова; викладання іноземної мови; професійно-орієнтоване навчання; майстерність; высшее образование; иностранный язык; преподавание иностранного языка; профессионально-ориентированное обучение; профессионализм